Minat Berwirausaha Mahasiswa : Pemahaman Kemajuan Teknologi E-Commerce Dan Pemahaman Marketplace - Erawati, Teguh; Cahyaningsih, Fitri (Universitas Hamzanwadi, 2025)
The influence of the industrial revolution 4.0 on the economy can be seen from the convenience offered by technological systems in the fields of trade and services. Nowadays, people can make transactions anytime and anywhere via the internet and electronically which results in increased efficiency and productivity as the background for carrying out this research. This research was carried out to find out how much influence understanding advances in e-commerce technology and understanding the marketplace has on students' interest in entrepreneurship in the Accounting Study Program at Bachelorwiyata Tamansiswa University. The method used is a quantitative method and convenience sampling technique. The sample used was 140 respondents, namely students of the Accounting Study Program at Bachelorwiyata Tamansiswa University. Data were collected using a questionnaire using a Likert scale, then processed and analyzed using SPSS version 25. The analysis techniques used were descriptive analysis, classical assumption tests, partial (t), simultaneous (F), and coefficient of determination (R2). The test results prove that there is a significant influence between understanding advances in e-commerce technology and understanding the marketplace on students' entrepreneurial interest. Students of the Accounting Study Program at Bachelorwiyata Tamansiswa University should not compete to find work after graduating from college, but can become entrepreneurs to open up employment opportunities and reduce the number of unemployed in Indonesia